Aktualisasi konsep pembelajaran salaf ala az-zarnuji dalam Era modern - Abd Wahid (STAI Syaichona Moh. Cholil Bangkalan, 2017)
Ta'lim al-Tariq al-Ta'allum Muta'llim be a monumental books in the field of education that leads into learning Islamic education in Indonesia, especially boarding school. Ta'lim al-Tariq al-Ta'allum Muta'llim taught as a basic concept of the introduction of community learning for students. Meanwhile, the concepts of modern teaching and learning continued to emerge. The concept of modern teaching and learning offers the concept of teaching and learning more complete. The emergence of the concept of modern teaching and learning are then led to the rejection of the concept and the attitude of the Salaf learning. Many thought emerged that speak for this refusal. The concept of Islamic education proposed Az Zarnuji cover some concepts: (1) The philosophy of science; (2) Motivation to learn; (3) Selection Process science; (4) Respect for science and scholars; (5) etor learning, learning continuity; (6) The onset and intensity of learning and martinet; (7) resignation to God; (8) Time and time to learn; (9) Love and giving advice; (10) curiosity; (11) Wara '; (12) The cause memorized and forgotten; (13) The issue of sustenance and age.